Two new fungal genera (Diaporthales) found on Dipterocarpaceae in Thailand - Xia Tang; Xia Tang; Xia Tang; Yong-Zhong Lu; Yong-Zhong Lu; Lakmali S. Dissanayake; Ishani D. Goonasekara; Ishani D. Goonasekara; Ruvishika S. Jayawardena; Ruvishika S. Jayawardena; Yuan-Pin Xiao; Kevin D. Hyde; et al. (Frontiers in Microbiology, 2023)
Diaporthales is a species-rich order of fungi that includes endophytes, saprobes, and pathogens associated with forest plants and crops. They may also occur as parasites or secondary invaders of plant tissues injured or infected by other organisms or inhabit living animal and human tissues, as well as soil. Meanwhile, some severe pathogens wipe out large-scale cultivations of profitable crops, timber monocultures, and forests. Based on morphological and phylogenetic analyses of combined ITS, LSU, tef1-α, and rpb2 sequence data, generated using maximum likelihood (ML), maximum parsimony (MP), and MrBayes (BI), we introduce two new genera of Diaporthales found in Dipterocarpaceae in Thailand, namely Pulvinaticonidioma and Subellipsoidispora. Pulvinaticonidioma is characterized by solitary, subglobose, pycnidial, unilocular conidiomata with the internal layers convex and pulvinate at the base; hyaline, unbranched, septate conidiophores; hyaline, phialidic, cylindrical to ampulliform, determinate conidiogenous cells and hyaline, cylindrical, straight, unicellular, and aseptate conidia with obtuse ends. Subellipsoidispora has clavate to broadly fusoid, short pedicellate asci with an indistinct J- apical ring; biturbinate to subellipsoidal, hyaline to pale brown, smooth, guttulate ascospores that are 1-septate and slightly constricted at the septa. Detailed morphological and phylogenetic comparisons of these two new genera are provided in this study.